THE PIENINY KLIPPEN BELT: ITS TECTONIC STRUCTURE AND EVOLUTION - M. G. Leonov (Геодинамика и тектонофизика)
Many mobile belts contain narrow (a few kilometres wide) and elongated (several hundreds and thousands kilometres long) zones characterized by complicated tectonic interiors and intensive rock metamorphism. Such zones are important components of the crustal structure; they determine the internal divisibility of the crust and act as accommodation areas or buffers between fragments of the crust which differ in origin and have specific evolution features. The article describes the paleo-evolution and characteristics of the Pieniny klippen belt, a major tectonic structure of the Carpathians and one of the largest linear tectonic zones in the Alpine-Himalayan folded belt.